The diet of Pomacea canaliculata (Gastropoda: Ampullariidae) in its native habitat based on gut content and stableisotopes analysis - López van Oosterom, Vanesa (2016)
Pomacea canaliculata is native to Rio de la Plata basin, and it is invasive in most of South and Southeast Asia after accidental introduction during unsuccessful attempts to establish commercial aquaculture of this species, and being present, the number one pest of rice crops in the region. Investigations in its native habitat are still needed because fundamental issues of its trophic ecology remain unknown. The aim of this research was to study the diet of P. canaliculata in its natural habitat through gut content techniques and stable isotopes of 13C and 15N. Biological samples were taken from November 2009 to December 2010 in Carnaval stream, a characteristic Pampean stream. Samples for stable isotopes of 13C and 15N using of a mixing model were collected in November 2011. The trophic strategy diagram evinced a generalist diet with high consumption of detritus followed by the vascular plants and algae. The mixing model results indicated that the relative contribution to the diet was similar for all basal resources: fine and coarse particulate organic matter, epipelon and aquatic macrophytes (approximately 40 %). These results evidenced a strong dietary plasticity for the species.